GE_GERICHTE P/25193/2023 vom 13. Februar 2024 - GE Cour de justice (2024)
MOTIVATION DE LA DÉCISION;JOUR DÉTERMINANT;RECTIFICATION DE LA DÉCISION;CALCUL DU DÉLAI;FIN | CPP.82.al4; CPP.221.al1.letc; CPP.227.al7